Modeling and Simulation of Hybrid System - Kumar, Kanhaiya; Aggrawal, Tanya; Verma, Vishal; Singh, Suraj; Sing, Shivendra; Varshney, Lokesh (International Journal of Psychosocial Rehabilitation, 2020)
The article presented is a simulation, modeling and designing of a hybrid power generation system which is based on non-conventional (renewable) wind turbine energy and solar photovoltaic reliable sources. The primary system is the solar electric generator, which consist of six models and connected to each other in series, based on predicted P&O and is connected to a MPPT controller and AC/DC converter, system is associated with Permanent Magnet Synchronous Generator. The main purpose this article is serving is to interconnect system so that it generates maximum power for single auxiliary phase loading, and the solar PV generator and systems of wind turbines for simulation with using Simulink/ MATLAB. The result of this simulation indicates that the hybrid power system is planned for efficiency, stability, reliability and model. Wind Turbine and Solar PV from the use of a renewable energy source for maximum voltage generation. The solar photovoltaic saturation flow and an ideal factor.